2013
DOI: 10.1155/2013/314248
|View full text |Cite
|
Sign up to set email alerts
|

Do High Frequency Ultrasound Images Support Clinical Skin Assessment?

Abstract: High frequency ultrasound imaging has been reported as a potential method of identifying the suspected tissue damage in patients “at risk” of pressure ulceration. The aim of this study was to explore whether ultrasound images supported the clinical skin assessment in an inpatient population through identification of subcutaneous tissue damage. Skin on the heels and/or sacral coccygeal area of fifty vascular surgery inpatients was assessed clinically by tissue viability nurses and with ultrasound pre operativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Table shows that the abnormal tissue induced by repetitive loading was accompanied with “Mild change” to “Severe change” results from the both raters’ US evaluation. This supports the previous studies where the early PU can be indicated by US evaluation . However, normal tissue examined under histopathology also has US evaluation results “Mild change” to “Severe change”.…”
Section: Resultssupporting
confidence: 88%
“…Table shows that the abnormal tissue induced by repetitive loading was accompanied with “Mild change” to “Severe change” results from the both raters’ US evaluation. This supports the previous studies where the early PU can be indicated by US evaluation . However, normal tissue examined under histopathology also has US evaluation results “Mild change” to “Severe change”.…”
Section: Resultssupporting
confidence: 88%
“…Most images (79.7%) with abnormal ultrasounds did not have documentation of skin erythema in the clinical record. More recently Porter-Armstrong et al 20 evaluated whether HFUS supported clinical skin assessment in an inpatient population by comparing HFUS to clinical assessments of heel and sacral skin. They found that qualitative classification of ultrasound images did not match outcomes yielded through the clinical skin assessment.…”
mentioning
confidence: 99%
“…This information includes lumen and vessel dimensions, plaque morphology, and location, thus enabling determination of the degree of stenosis [ 11 ]. Additional studies reported that high frequency ultrasound imaging was a potential method for identifying the suspected tissue damage and vascular complications in patients at risk of pressure ulceration [ 12 , 13 , 14 ]. Porter-Armstrong et al explored whether ultrasound images supported clinical skin assessment in an inpatient population by identifying subcutaneous tissue damage [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies reported that high frequency ultrasound imaging was a potential method for identifying the suspected tissue damage and vascular complications in patients at risk of pressure ulceration [ 12 , 13 , 14 ]. Porter-Armstrong et al explored whether ultrasound images supported clinical skin assessment in an inpatient population by identifying subcutaneous tissue damage [ 13 ]. However, the study demonstrated that qualitative classification of ultrasound images did not match outcomes yielded through clinical skin assessment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%